A Little Queue Theory. - Armour, Phillip G. (Communications of the ACM, 2015)
The article looks at workload and project management, focusing on software development projects. The author criticizes the tendency of project managers to create long task lists for each project participant and to schedule a very high percentage of each one's time. Drawing on queue theory, he suggests doing so can actually result in problems that make software development projects take longer to complete.